2014
DOI: 10.1213/ane.0000000000000002
|View full text |Cite|
|
Sign up to set email alerts
|

Consensus Guidelines for the Management of Postoperative Nausea and Vomiting

Abstract: The present guidelines are the most recent data on postoperative nausea and vomiting (PONV) and an update on the 2 previous sets of guidelines published in 2003 and 2007. These guidelines were compiled by a multidisciplinary international panel of individuals with interest and expertise in PONV under the auspices of the Society for Ambulatory Anesthesia. The panel members critically and systematically evaluated the current medical literature on PONV to provide an evidence-based reference tool for the managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
1,098
3
40

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,278 publications
(1,162 citation statements)
references
References 251 publications
21
1,098
3
40
Order By: Relevance
“…No differences were noted between methylprednisolone and dexamethasone in postoperative pain, oral intake and alimentation scores but with a follow-up limited to the first 24 postoperative hours [20]. The dose of dexamethasone used in our study is in agreement with guidelines recently reassessed [21] for PONV prophylaxis. A prospective study found a 57.5% reduction in severe pain on POD2 with a single dose of dexamethasone at 0.15 mg/kg compared to placebo, with a prolonged decrease of PONV during the first two postoperative days [22].…”
Section: Discussionsupporting
confidence: 83%
“…No differences were noted between methylprednisolone and dexamethasone in postoperative pain, oral intake and alimentation scores but with a follow-up limited to the first 24 postoperative hours [20]. The dose of dexamethasone used in our study is in agreement with guidelines recently reassessed [21] for PONV prophylaxis. A prospective study found a 57.5% reduction in severe pain on POD2 with a single dose of dexamethasone at 0.15 mg/kg compared to placebo, with a prolonged decrease of PONV during the first two postoperative days [22].…”
Section: Discussionsupporting
confidence: 83%
“…In addition, antiemetics are more efficacious when administered toward the end of surgery rather than at anesthesia induction. Furthermore, consensus guidelines for PONV recommend multimodal prophylaxis to prevent PONV in high-risk patients [23]; further studies are therefore required to evaluate the potential usefulness of this drug in combinations with other antiemetics.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of PONV can be as high as 80% in high-risk patients with incidence of vomiting about 30% and nausea about 50% [24]. PONV can result in extended postanesthesia care unit (PACU) stay with unforeseen hospital admission so we see that PONV results in a significant increase in overall care costs.…”
Section: Ponv Avoidance and Treatmentmentioning
confidence: 97%